2022
DOI: 10.1007/s11104-022-05634-8
|View full text |Cite
|
Sign up to set email alerts
|

Combination of humic biostimulants with a microbial inoculum improves lettuce productivity, nutrient uptake, and primary and secondary metabolism

Abstract: Background and aims Biostimulants of natural origin represent a growing ecological strategy to increase crops productivity, especially when applied in combination with microbial bioeffectors. We studied the effect of biostimulants such as Potassium Humates (KH) from Leonardite and Compost Tea (CT) from green compost on both productivity and nutritional status of lettuce plants, as well as on the primary and secondary metabolism of treated plants, when amended either alone or in combination with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 143 publications
1
7
0
Order By: Relevance
“…Accordingly, treatment with GA and GA + HA resulted in a significant accumulation of flavanols. Similar results were highlighted by Savarese et al [43], where the use of HA in combination with a microbial inoculum on lettuce significantly affected both primary and secondary metabolism, increasing the biosynthesis of essential amino acids, carbohydrates, and polyphenolic compounds.…”
Section: Metabolomic Profiling Of Lettuce Treated With Glutamic Acid ...supporting
confidence: 86%
“…Accordingly, treatment with GA and GA + HA resulted in a significant accumulation of flavanols. Similar results were highlighted by Savarese et al [43], where the use of HA in combination with a microbial inoculum on lettuce significantly affected both primary and secondary metabolism, increasing the biosynthesis of essential amino acids, carbohydrates, and polyphenolic compounds.…”
Section: Metabolomic Profiling Of Lettuce Treated With Glutamic Acid ...supporting
confidence: 86%
“…Numerous studies have confirmed the beneficial effects of HA and FA on plant yielding [35], nutrient metabolism, and the synthesis of compounds involved in plant adaptation to stress factors [28,33,36]. What is more, humic substances promote seed germination and seedling development [37,38] and root growth [39,40] and increase the cell membrane permeability and stimulate the synthesis of nucleotides [41], chlorophyll [42], proteins, and monosaccharides [35]. Thanks to its ability to bind and precipitate harmful substances, soil humus also serves a protective function in the environment [43] and affects the behaviour and availability of trace elements in the soil [44].…”
Section: Introductionmentioning
confidence: 93%
“…They mainly increase the phytoavailability of phosphorus, potassium, magnesium, iron, and zinc [33,34]. Numerous studies have confirmed the beneficial effects of HA and FA on plant yielding [35], nutrient metabolism, and the synthesis of compounds involved in plant adaptation to stress factors [28,33,36]. What is more, humic substances promote seed germination and seedling development [37,38] and root growth [39,40] and increase the cell membrane permeability and stimulate the synthesis of nucleotides [41], chlorophyll [42], proteins, and monosaccharides [35].…”
Section: Introductionmentioning
confidence: 97%
“…Lastly, additional in vivo studies are needed to confirm the efficacy of HS-FEN, in order to verify the potentiality of humic substances from composted green biomasses, not only in agricultural sector as biostimulants [67], but also in medical field.…”
Section: Limitations Of Studymentioning
confidence: 99%